Supply chain management: Solutions to improving the competitive advantage of small- and medium-sized enterprises: The case of Danang City - Lê, Th? Minh H?ng (University of Economics Ho Chi Minh City, 2023)
Supply chain management (SCM) has been proven to improve the competitive advantage, and increase the effectiveness of operation in small and medium sized enterprises (SMEs) (Chin et al., 2012). This study investigates the measurement of SCM practice in Vietnam with the sample of 148 SMEs in Danang. The research findings exhibit the humble degree of SCM practices within these firms. These activities are in the primary form of SCM practice as supplier’s quality management, customer interaction, and customer satisfaction measurement. The findings also indicate the limitations in practicing SCM in Danang SMEs, and propose implications in policy adjustment to promote SCM practices and advance the competitive advantages of SMEs.